Biopoetics Towards an Existential Ecology - Weber, Andreas (Biosemiotics,, 2016)
Meaning, feeling and expression - the experience of inwardness - matter most in human existence. The perspective of biopoetics shows that this experience is shared by all organisms. Being alive means to exist through relations that have existential concern, and to express these dimensions through the body and its gestures. All life takes place within one poetic space which is shared between all beings and which is accessible through subjective sensual experience. We take part in this through our empirical subjectivity, which arises from the experiences and needs of living beings, and which makes them open to access and sharing in a poetic objectivity. Biopoetics breaks free from the causal-mechanic paradigm which made biology unable to account for mind and meaning. Biology becomes a science of expression, connection and subjectivity which can understand all organisms including humans as feeling agents in a shared ecology of meaningful relations, embedded in a symbolical and material metabolism of the biosphere.